Perceptions des étudiants en ergothérapie et en travail social quant au développement de leurs compétences interculturelles durant la formation initiale - Sylvie Tétreault; Camille Brisset; Carine Bétrisey; Alida Gulfi; Yvan Leanza; Nicolas Kühne
Health and social professionals interact with a wide diversity of populations (age, geographic origin, language, religion, health status, socio-economic background, etc.), which can change the way they intervene. The present study aims to explore students' perceptions of occupational therapy and social work related to the development of their intercultural competencies, including their strategies implemented in order to work harmoniously with an individual with a significant difference. Forty-six people participated in an annual interview during their three years of training. Based on the transformative learning model, a thematic analysis allowed to identify seven themes evoked by participants on this topic: (1) identify learning and areas to improve; (2) strengthen one's self-confidence; (3) use communication techniques effectively; (4) deal with aggression or divergent ideas; (5) know and adapt to the Other; (6) integrate and apply theoretical knowledge; (7) be able to question oneself. Recommendations for training are made.